(untitled) (Architecture Image Studies, 2026)
Stroke is a major cause of long-term disability, requiring active caregiver involvement in rehabilitation. In low-income communities, limited access to formal training reduces caregiver competence in performing motor exercises such as Range of Motion (ROM), which are essential for preventing joint stiffness and promoting recovery. This study aimed to develop and evaluate the effectiveness of INBELMOTO, a print-based educational intervention, in improving the knowledge and motor training skills of stroke caregivers. A one-group pretest–posttest design was conducted on 40 caregivers of stroke inpatients at Purwokerto Islamic Hospital, Central Java. The booklet was validated by 12 multidisciplinary experts (I-CVI = 0.958). Caregivers used the material during a three-day inpatient period. Knowledge and motor skills were assessed before and after the intervention. Mean knowledge scores increased from 87.48 to 90.78, and motor skills from 23.75 to 28.78. Knowledge improvement was not statistically significant (p = 0.070), but motor skills showed a significant increase (z = –4.278; p < 0.001; r = –0.98). INBELMOTO is a promising low-cost educational tool for enhancing caregiver motor training skills. Future efforts should integrate this approach with audiovisual and hands-on guidance for better outcomes.